2021
DOI: 10.1038/s41598-021-97365-6
|View full text |Cite
|
Sign up to set email alerts
|

The prognosis and clinicopathological features of different distant metastases patterns in renal cell carcinoma: analysis based on the SEER database

Abstract: Existing data on the prognosis and clinicopathological features of patients with metastatic renal cell carcinoma (mRCC) are limited. This study aims to investigate the prognostic value and clinicopathological features of different metastatic sites in patients with mRCC. A dataset from the National Cancer Institute’s Surveillance, Epidemiology, and End Results (SEER) database consisting of 18 registries (1973–2015) was selected for a retrospective mRCC cohort study. Information was included on the metastatic si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 26 publications
2
19
0
2
Order By: Relevance
“…Additionally, variation in diagnostic protocols, data collection and follow-up protocols between participating centers may introduce further confounding and limitation. We acknowledge that our findings did not demonstrate location of metastasis to be associated with worsened outcomes as has been previously demonstrated in mRCC and other genitourinary malignancies which may be a result of sampling bias ( 31 33 ). Nonetheless, AUC demonstrated robust predictive ability comparable to existing risk stratification criteria for oncologic outcomes in metastatic RCC, and the diverse nature of this international registry and the robustness of the findings lend support to the validity and applicability of our findings.…”
Section: Discussionsupporting
confidence: 64%
“…Additionally, variation in diagnostic protocols, data collection and follow-up protocols between participating centers may introduce further confounding and limitation. We acknowledge that our findings did not demonstrate location of metastasis to be associated with worsened outcomes as has been previously demonstrated in mRCC and other genitourinary malignancies which may be a result of sampling bias ( 31 33 ). Nonetheless, AUC demonstrated robust predictive ability comparable to existing risk stratification criteria for oncologic outcomes in metastatic RCC, and the diverse nature of this international registry and the robustness of the findings lend support to the validity and applicability of our findings.…”
Section: Discussionsupporting
confidence: 64%
“…Although the treatment of mRCC has made progress in the past two decades, the prognosis of patients with mRCC remains dismal ( 15 ). Previous studies on mRCC generally concentrated on the long-term survival of patients ( 16 , 17 ) or risk factors related to lung and bone metastasis ( 18 , 19 ). However, advanced or highly invasive tumors often lead to early death and few study has identified risk factors associated with early death in mRCC.…”
Section: Discussionmentioning
confidence: 99%
“…However, while the range of neurologic and cognitive symptoms may be large among metastatic brain tumor patients, the development of BM typically portends poor overall prognosis. For example, median survival for renal cell carcinoma patients with BM was 5 months, and the median survival for patients with solid BM from non-small cell lung cancer was 8.4 months ( 7 , 8 ).…”
Section: Challenges Of Living With Brain Metastasesmentioning
confidence: 99%